1978
DOI: 10.1084/jem.148.5.1198
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous murine lupus-like syndromes. Clinical and immunopathological manifestations in several strains.

Abstract: MRL/1 and BXSB male mice have a systemic lupus erythematosus (SLE)-like disease similar to but more acute than that occurring in NZB X W mice. The common elements of lymphoid hyperplasia, B-cell hyperactivity, autoantibodies, circulating immune complex (IC), complement consumption, IC glomerulonephritis with gp70 deposition, and thymic atrophy were found in all three kinds of SLE mice. On the basis of these common elements, SLE seen in these mice can be considered a single disease in the same sense that human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
772
2
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,448 publications
(818 citation statements)
references
References 23 publications
31
772
2
4
Order By: Relevance
“…43 Moreover, the role of IL-21 is also shown in another model of murine lupus, NZB/W F1 mice, which exhibit clinical features that resemble those of human SLE, including autoantibody production and immune complex-mediated nephritis. 44,45 Upon intranasal administration of anti-CD3 antibodies, NZB/W F1 mice exhibited suppressed lupus development characterized by reduced levels of autoantibodies and diminished glomerulonephritis. 45 It was found that the treatment with anti-CD3 antibody affected the function of CD4 1 CXCR5 1 ICOS 1 T FH cells, characterized by decreased IL-21 and IL-17 production in these mice which was associated with the autoimmune pathologies.…”
Section: T Fh Cells In Murine Models Of Autoimmune Diseasesmentioning
confidence: 99%
“…43 Moreover, the role of IL-21 is also shown in another model of murine lupus, NZB/W F1 mice, which exhibit clinical features that resemble those of human SLE, including autoantibody production and immune complex-mediated nephritis. 44,45 Upon intranasal administration of anti-CD3 antibodies, NZB/W F1 mice exhibited suppressed lupus development characterized by reduced levels of autoantibodies and diminished glomerulonephritis. 45 It was found that the treatment with anti-CD3 antibody affected the function of CD4 1 CXCR5 1 ICOS 1 T FH cells, characterized by decreased IL-21 and IL-17 production in these mice which was associated with the autoimmune pathologies.…”
Section: T Fh Cells In Murine Models Of Autoimmune Diseasesmentioning
confidence: 99%
“…Genetic analysis of disease in relation to the development of arthritis and of anti-Sm antibodies has shown that up to ෂ25% develop one or other of these manifestations depending on the colony and without known genetic factor. 54 This observation suggests that unknown environmental factors may be responsible for the development of these features.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…The disease is spontaneous, more severe and develops earlier in females (at ෂ4-5 months of age) 53 ; high titres of IgG anti-DNA antibodies, antinuclear antibodies (ANA) occurs in virtually all females and death results from progressive glomerulonephritis. 54 The disease in the BWF1 mouse is particularly sensitive to the effects of sex hormones; in general, androgens are protective and suppress the production of autoantibodies whereas estrogens are permissive. 55,56 Both NZB and NZW parents contribute genetically to the immune abnormalities that cause disease.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
See 1 more Smart Citation
“…This gene is also known to induce various forms of rheumatic disease, including glomerulonephritis, vasculitis, and arthritis, in the presence of an MRL genetic background (8)(9)(10). Recently, it was shown that the lpr gene is a deletion mutant of the Fas antigen (1 1).…”
mentioning
confidence: 99%